Exploring the Impact of Retention Strategies on job Satisfaction and Organizational Commitment in Commercial Banks of Khyber Pakhtunkha, Pakistan - YASIR KHAN; MUHAMMAD SHAFIQ GUL; MUKHARIF SHAH (Journal of Business & Tourism, 2021)
This research has been conducted at knowing the effects of retention strategies on job satisfaction and employees commitment. This research was conducted employees of this sector switching more often to other banks , as this sector is very volatile and all banks prefer to use most effective retention strategies in better dealing, satisfying and committing employees. This research will really help the top level management in knowing the efficacy of its retention strategies worth. The data was collected through questionnaires used by other researchers for their studies before. The scale used has been mentioned in in the construct of this study. This research used job satisfaction and commitment as dependent variable and the retention strategies as independent variable. Reliability analysis conducted for the purpose of the reliability of the data.Thus the research achieved both of the hypotheses that the retention strategies have positively effectjob satisfaction and organizational commitment of employees.